Investigating the function of LRB-interacting proteins in Arabidopsis thaliana - Montpetit, Jordan T. (My University, 2011)
The Gingerich lab has found that Arabidopsis thaliana contains two proteins, LRB1 and LRB2 which also act in red light signaling. Arabidopsis plants with both of these genes disrupted are overly sensitive to red light (and therefore shade tolerant). In attempt to better understand LRB1 and LRB2's function, this study conducted a type of protein-protein interaction screen known as a yeast two-hybrid screen with these two proteins.
Color poster with text, images, and graphs.
Keywords: Arabidopsis thaliana--Effect of light on; Plant proteins--Research; Phytochrome; Posters